Atomically targeting NiFe LDH to create multivacancies for OER catalysis with a small organic anchor. (March 2021) - Wang, Yaqiong; Tao, Shi; Lin, He; Wang, Gaopeng; Zhao, Kangning; Cai, Rongmin; Tao, Kewen; Zhang, Chengxu; Sun, Mingzi; Hu, Jue; Huang, Bolong; Yang, Shihe
Abstract: The fabrication of porous structure in the ultrathin materials still faces high difficulties. In particular, the precise modulations in the porosity and size are highly challenging. In this work, we have introduced small molecules to overcome such a challenge. And this substantially contributes to the energy related applications, especially to the water-energy (WE) treatment. Electrocatalytic water-splitting is hindered by the sluggish kinetics of water oxidation, requiring efficient earth-abundant electrocatalysts for the oxygen evolution reaction (OER). Herein we demonstrate the robust OER activity by introducing metal and oxygen multivacancies in noble-metal-free layered double hydroxides (LDHs) through the specific electron-withdrawing organic molecule methyl-isorhodanate (CH3 NCS). Our work reveals that the metal and oxygen vacancies endow NiFe LDH with enhanced electron transfer and modulate the H2 O adsorption, thereby boosting the OER electrocatalytic properties. Remarkably, the best-performing laminar NiFe LDH nanosheets with metal and oxygen multivacancies ( v -L -LDHs) show an ultra-low overpotential of 230 mV at 100 mA cm −2 and Tafel slope of 37.1 mV dec −1 . Density functional theory (DFT) has revealed the improved OER performance is realized by the co-existence of metal and O vacancies in NiFe LDH, where the defective region activates the electroactivity of Ni sites and O sites to promote the electron transfer and intermediate transformation. The Fe sites play a key role to preserve the high electroactivity of the Ni sites in long-term applications. The superior OER performance underpins the high potential of the reported facile organic anchor strategy for designing and synthesizing advanced electrocatalysts in both LDH and other potential 2D layered materials. Graphical Abstract: ga1 Highlights: The simple approach based on the small molecule to create vacancies in LDH is reported for the first time. The co-existence of metal and oxygen vacancies significantly boosts the electroactivity of LDH. DFT calculations confirm activations of electroactivity by the formation of both oxygen and metal vacancies.